Misogynistic in the K-Pop Industry: Analyzing Gender Bias Towards Female Idols - Zahra, Alyssa Aydina (Serat: Journal of Literary & Cultural Studies, 2024)
Misogyny has always been a problem in the K-Pop industry. Those misogynistic acts include holding female idols to strict beauty standards, unequal treatments, and harassing and objectifying them. This study focuses on how misogyny functions in the K-Pop industry through content analysis of media representations. It examines how companies treat female idols, how they are portrayed, and how gender dynamics affect their career path. The purpose of this study is to provide a viewpoint of the unequal treatment of women in K-Pop due to their gender, the cause of this as well as how it impacts their mental health, and also to explore the perspective and experiences of female idols as they navigate the patriarchal norms attached in the industry. The results along with the analyses of the study show that misogyny is a familiar issue in the K-Pop industry by showing how female idols are facing unequal treatment and pressure to meet nonsense and strict beauty standards. Also, the harassment and objectification they experienced limited their freedom. This study points out how important it is to talk about misogyny in K-Pop in order to achieve fair treatment and protect their rights.